Pál Sárváry’s Contribution to the Teaching of the Natural Sciences at the Reformed College of Debrecen, with Special Emphasis on His Book Entitled Philosophical Ethics - MAGYAR, Balázs Dávid (Studia Universitatis Babes-Bolyai Theologia Reformata Transylvanica, 2025)
According to the Hungarian lexicons and handbooks, Pál (Paul) Sárváry was a famous Hungarian painter and graphic architect. The higher seminaries at the Reformed College of Debrecen were started by him in 1782. Sárváry put specific emphasis on the acquirement of the German language and of the rhetorical arts. After a short stay in the city of Késmárk, he returned to Debrecen in order to serve as a lecturer of poetry. As his personal diaries reveal, he was involved in the tradition of peregrination. His destination was the University of Gottingen, where he fulfilled the requirements of the doctoral examination. After his successful exam, Sárváry visited the educational centres of Jena, Halle, Leipzig, Wittenberg, Berlin, London, Oxford, Utrecht, Regensburg, and Vienna. We find him in Debrecen again in 1795, when he was accepted as teacher of mathematics, physics, and philosophy. Although Sárváry was a celebrated personality of poetry, painting, geology, and architecture in Debrecen, it is worth focusing on a particular piece of his little-known philosophical heritage, namely Philosophical Ethics (1804), in order to illuminate his philosophical and theological thinking.